(3JChjdGJ Cgd GdSfIs - (3eMeO Hf eMeO Hf eMehO, CHh efUhQ GdneGoJpQjOj,J (B333 (3g` s
(3ChdgG (B:s
(3jHJOF HShQI GdCYQGa s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI (B" (3GdQYO (B" s
(3LRA efgs
(3Ydjg Jedc eDQN HSfI (B818 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B19 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B300s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B25 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B335s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs